Ultrafiltration pretreatment enhances membrane distillation flux, resilience and permeate quality during water recovery from concentrated blackwater (urine/faeces) - Kamranvand, Farhad; Davey, Christopher J.; Williams, Leon; Parker, Alison; Jiang, Y.; Tyrrel, Sean; McAdam, Ewan J. (Elsevier, 2020)
In this study, the pretreatment of concentrated blackwater using ultrafiltration (UF) was shown to improve the permeability, selectivity and robustness of membrane distillation (MD) for application to wastewater treatment. Concentrated blackwater comprises urine and faeces, with minimal flushwater added. The faecal contribution increased the soluble organic fraction and introduced coarse and colloidal particles into the urine, which increased resistance to filtration during dead-end UF. Ultrafiltration removed the particulate and colloidal fractions (MW > 500 kDa) from the blackwater, which permitted similar permeability and robustness for MD to that observed with urine (29.9 vs 25.9 kg m−2 h−1), which comprises a lower colloidal organic concentration. Without UF pretreatment, a higher density organic layer formed on the MD surface (197 vs 70 gCOD m−2) which reduced mass transfer, and transformed the contact angle from hydrophobic to hydrophilic (144.9° to 49.8°), leading to pore wetting and a dissipation in product water quality due to breakthrough. In comparison, with UF pretreatment, MD delivered permeate water quality to standards satisfactory for discharge or reuse. This is particularly timely as the ISO standard for non-sewered sanitation has been adopted by several countries at a national level, and to date there are relatively few technologies to achieve the treatment standard. Membrane distillation provides a robust means for concentrated blackwater treatment, and since the energy required for separation is primarily heat, this advanced treatment can be delivered into areas with more fragile power networks.
Keywords: Urine; Faeces; Sanitation; Single-household; Fouling; Ammonia